State-wide surveillance of antibiotic resistance patterns and spa types of methicillin-resistant Staphylococcus aureus from blood cultures in North Rhine-Westphalia, 2011–2013. (August 2015) - Cuny, C.; Layer, F.; Werner, G.; Harmsen, D.; Daniels-Haardt, I.; Jurke, A.; Mellmann, A.; Witte, W.; Köck, R.
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a major cause of bacteraemia. We aimed to obtain a complete picture of severe MRSA infections by characterizing all MRSA isolates from bloodstream infections in the largest German federal state (North Rhine-Westphalia, 18 million inhabitants) using S. aureus protein A ( spa ) sequence-typing and antimicrobial susceptibility testing. MRSA isolates ( n  = 1952) were collected prospectively (2011–2013) and spa -typed. Among 181 different spa types, t003 ( n  = 746 isolates; 38.2%) and t032 ( n  = 594; 30.4%) were predominant. Analysis of the geographical occurrence of spa clonal complexes ( spa -CCs) and spa types revealed divergent distribution between federal state districts for spa -CCs 003 (p < 0.001; including t003, p < 0.001 and t264, p < 0.001), 008 (p 0.021), 011 (p 0.002), 032 (p < 0.001; including t022, p 0.014 and t032, p < 0.001) and spa type t2807 (p < 0.001). MICs of antimicrobial substances were tested using broth microdilution. Of all isolates, 96% were resistant to fluoroquinolones, 78% to erythromycin, 70% to clindamycin, 4% to gentamicin, 2% to rifampicin, 0.4% to daptomycin, 0.1% to linezolid and 0% to vancomycin, respectively. Vancomycin MICs of 2 mg/L involved 0.5% of the isolates. In conclusion, the detection of regional molecular clusters added valuable information for epidemiological case tracing and allowed conclusions to be reached on the importance of newly emerging MRSA reservoirs, such as livestock ( spa -CC011), for MRSA bacteraemia in some parts of the federal state. Susceptibility testing revealed broad resistance to substances used for oral treatment, but demonstrated that those antibiotics that are mostly applied for treatment of MRSA bacteraemia and important combination partners were highly susceptible.